Toxicity and α-Glucosidase Inhibitory Activity of Chromolaena odorata L. for Antidiabetic Herbal Tea - Soufa Malita; Muhammad Junaedi (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2026)
Background: Coppasanda (Chromolaena odorata) is a weed plant containing secondary metabolites with potential antidiabetic activity by lowering blood glucose levels. This plant has been developed into a tea bag formulation. Previous studies reported that Coppasanda tea significantly reduced blood glucose levels in alloxan-induced rats; however, higher concentrations caused unstable glucose levels. Therefore, toxicity testing and α-glucosidase inhibitory assays are required to evaluate its safety and enzyme-inhibiting potential. Objectives: This study aimed to determine the toxicity profile and α-glucosidase inhibitory activity of Coppasanda tea bags. Methods: Acute toxicity testing was conducted in vivo using 30 mice divided into five groups: control (0.5% CMC-Na), P1 (50 mg/kg BW), P2 (300 mg/kg BW), P3 (1000 mg/kg BW), and P4 (2000 mg/kg BW). The α-glucosidase inhibition assay was performed in vitro using p-nitrophenyl-α-D-glucopyranoside (pNPG) as the substrate and α-glucosidase enzyme. Absorbance was measured using a spectrophotometer at 405 nm. Results: The toxicity test showed no toxic symptoms of Coppasanda tea bags, indicated by the absence of significant changes (P > 0.05) in body weight, mortality, clinical signs, and organ indices of the experimental animals. In vitro results demonstrated strong α-glucosidase inhibitory activity, with a maximum inhibition of 98% and an IC₅₀ value of 29 µg/mL. Conclusion: Coppasanda tea bags are non-toxic and exhibit strong α-glucosidase inhibitory activity, indicating potential as a safe antidiabetic herbal beverage.